Manifesta and us. - Boubnova, Iara; Prashkov, Kiril; Kiossev, Alexander; Eraso, Santiago; Troncy, Eric; Institute of Contemporary Art, Sofia (Sofia : Institute of Contemporary Art, 2003)
Solakov, Nedko ; Galev, Galentin ; Ivanov, Pravdoliub ; Boyadjiev, Luchezar ; Serapionov, Kalin ; Moudov, Ivan
Institute of Contemporary Art, Sofia, 2003.
kunstcatalogus